Dynamic evaluation of hemostasis in the acute phase of Kawasaki disease using comprehensive coagulation functional assays. Issue 174 (February 2019) - Yoshizawa, Hiroyuki; Nogami, Keiji; Matsumoto, Tomoko; Tsujii, Nobuyuki; Sakai, Toshiyuki; Takase, Toshio; Tanaka, Ichiro; Shima, Midori
Abstract: Introduction: Kawasaki disease (KD) is a systemic vasculitis involving coronary arteries, sometimes resulting in aneurysms and myocardial infarction. Hyper-coagulability in the acute-phase of KD is indicated in some circumstances based on changes of individual clotting factors. Comprehensive coagulation assays, clot waveform analysis (CWA) and thrombin/plasmin generation assay (T/P-GA), have been developed to assess physiological hemostasis, but these techniques have not been applied in KD. Methods: We utilized both assays to analyze coagulation function in KD children ( n  = 42) prior to intravenous-immunoglobulin (IVIG) treatment (Pre), 1-week (1W) and 1-month (1M) post-IVIG. Results: In CWA, the clot time (CT) pre-treatment was prolonged, and was significantly shortened at 1W and 1M. However, the maximum coagulation velocity (|min1|) and acceleration (|min2|) were ~2-fold greater relative to controls, indicating an overall hypercoagulable tendency. These parameters were related to fibrinogen concentration, and were decreased at 1W and declined to normal at 1M. In T/P-GA, the endogenous potentials of thrombin and plasmin were greater relative to control at each of three time-points, and measurements at 1W were greater than those Pre-treatment. The ratios of TG and PG relative to control were similar, however, suggesting well-balanced dynamic coagulation and fibrinolysis. In non-responders to IVIG, the |min1| and |min2| measurements were greater than those in responders at 1W and 1M, suggesting that non-responders remained hypercoagulable after primary treatment. Conclusion: The coagulation data observed in KD were consistent with hypercoagulability, although fibrinolytic function appeared to be well-balanced. Comprehensive assays of this nature could provide valuable information on coagulation potential in KD. Highlights: We assessed the global coagulation/fibrinolysis potentials in Kawasaki disease (KD). An overall hypercoagulable tendency was shown in acute phase of KD. Hypercoagulability in KD seemed likely to be balanced with fibrinolytic function. Non-responder to immunoglobulin remained hypercoagulable after primary treatment.